Attitudes, Perceptions of Ability, Barriers, and Expectations of Lecturers in the Use of ICT in Online English Learning - Apriani, Eka; Arsyad , Safnil; Syafryadin, Syafryadin; Baihaqi, Yasmika; Wijayanti, Erfin; Esmianti, Farida; Supardan, Dadan (Journal of English Education and Teaching, 2025)
This study aims to analyze the attitudes, perceptions of abilities, barriers, and expectations of IAIN Indonesia lecturers in the use of ICT in online English learning. The research method uses "explanatory sequential". The research sample was selected randomly and purposively. Questionnaires and interviews are used to collect the data. The quantitative data were analyzed by the SPSS program, while the interview findings were analyzed qualitatively. 80% of lecturers had positive views toward ICT use during class planning, according to the results (M = 4.2, SD = 0.7). They were thought to have a modest level of ICT proficiency, especially when it came to implementing lessons (M = 3.92, SD = 0.86). According to reports, there were few obstacles, mostly because of inadequate training and a lack of teaching facilities (M = 2.3, SD = 1.1). Expectations were high, particularly with regard to ongoing training and access to ICT infrastructure (M = 4.45, SD = 0.8). The results of this study in general, provide an overview of the attitudes and abilities that must be possessed by lecturers to minimize challenges in the hope of realizing the optimal use of ICT in online English learning.